Hydrogen supply chain modelling at energy system scale: A review - Fabio Bozzolo Lueckel; Rory Monaghan; Muireann Á. Lynch (The Economic and Social Research Institute (ESRI), 2023)
Hydrogen is going to play an important role in future decarbonized energy systems and understanding its interaction with other energy vectors is crucial to create adequate policies. In this review, the green hydrogen production literature was classified and analysed to unveil the gaps that avoid a proper integration of hydrogen production in energy system models. Production-side supply chain (PSSC) and systems side impact (SSI) models were analysed. Based on site-specific models, the former showed detail on the optimization of the supply chain, whereas the latter on the impact of hydrogen deployment in an energy system. The first challenge identified is the variables considered, where inherent endogenous variables of one type of model were exogenized in their counterpart model. This is relevant because of the unique geographical characteristics of the sites and the effect of the large-scale production of hydrogen on the energy system. Further, PSSC models tend to consider a profit maximization approach and SSI model, cost minimization. The first normally does not consider social externalities in their investment decisions and the latter neglects the effect of competition between different players in the market. Moreover, the computational requirements of a cost minimization approach are less demanding and complex than a profit maximization approach at a large-scale. Other gaps found included; a lack of life-cycle assessment and the effect of large-scale hydrogen facilities integrated into SSI. This study reveals gaps in the current hydrogen modelling literature that need to be addressed for defining the future of energy systems' decarbonization.
Keywords: 330; Hydrogen; Energy Systems; Supply chain; Optimization; Modelling; Integration; Renewable